The Impact of Cardiac Telerehabilitation on Health-Related Quality of Life in Patients Undergoing Percutaneous Coronary Intervention (PCI): A Systematic Review Protocol - Francesco Limonti; Andrea Gigliotti; Francesco Gravante; Nicola Ramacciati (Nursing Reports)
Background: Cardiac rehabilitation (CR) is an intervention to improve health and quality of life in patients undergoing percutaneous coronary intervention (PCI). The use of digital technology for healthcare promotion, such as telemedicine, has received growing attention in recent years due to the possibility of offering remote and individualized cardiac rehabilitation to patients undergoing coronary interventions. However, the impact of cardiac telerehabilitation on health-related quality of life (HRQoL) is not fully understood. This systematic review aims to analyze through meta-analyses and synthesized comments the current knowledge on the effectiveness of cardiac telerehabilitation in improving HRQoL in patients undergoing PCI. Objectives: This manuscript presents a protocol for a systematic review to assess the effects of cardiac telerehabilitation on HRQoL in cardiac patients after PCI. Furthermore, the systematic review will explore the different modalities of remote rehabilitation documented in scientific literature. Methods: The literature review protocol was developed according to the PRISMA guidelines for systematic reviews. Search terms were structured according to the PIO (Population-Intervention-Outcome) framework. All relevant available studies will be identified using the main databases (PubMed, Scopus, CINAHL, Web of Science, and the Cochrane Library) and included in the review. Methodological quality and risk of bias will be evaluated using the Crowe Critical Appraisal Tool (CCAT). This review protocol has been registered on PROSPERO (No. CRD42024582933). Conclusions: This systematic review will comprehensively investigate the effects of cardiac telerehabilitation on QoL improvements in patients after PCI.